PENINGKATAN MINAT BELAJAR PADA PEMBELAJARAN BAHASA INDONESIA MELALUI PENGGUNAAN MEDIA (Autosaved) - Wulandari, sri; Nitbani, Samuel H.; Muli, Margarita T. B. (Jurnal Lazuardi, 2024)
ABSTRACT The purpose of this research is to 1) use envelope media to enhance reading interest in learning Indonesian, 2) evidence using envelopes media can stimulate student reading interest. This research is Research Action Class at SMAN 3 Kupang, class XA semester 1 year lesson 2023/2024 carried out from September 2023 s.d February 2024. Data collection techniques used are in-depth interviews, observations, and documentation. Data analysis techniques use critical analysis and interactive analysis. The results of the study showed that the lowest scores in cycle I were the minimum 65, the highest 85, the average 72, the number of students who graduated 23 and who were not 13. In cycle II, the minimum scores were 68, the maximum 92, the average was 78, students who were graduated 33 and who had not had three children. Based on the results of the use of this envelope media, it can be said that learning with this strategy should be developed and implemented in the process of learning Indonesian language, in particular in improving student reading skills. Keywords: interest in learning, Indonesian, envelope media